ONLINE LEARNING TECHNOLOGIES: CREATIVE-AUTHORIZED METHOD - L. Ushvitsky; A. Stepanov; M. Savina (Вестник Северо-Кавказского федерального университета, 2022)
The author proposed the methodology «Creative-authorized-distance learning» (KADO) as a new educational technology based on providing students with independence and unlimited opportunities for mobilization (activation) of subjective cognitive-creative potential. The goal of KADO is to create an environment of creative energy that involves students in the process of self-learning. The article suggests innovative tools and methods for delivering theoretical and practical material using Internet technologies, discloses the features of the educational process organization in the distance learning algorithm, taking into account territorial and temporary disunity using a specific set of procedures, methods and forms of educational process organization.